Experiences of and resistance to multiple discrimination in health care settings among transmasculine people of color - Madina Agénor; Sophia R. Geffen; Dougie Zubizarreta; Raquel Jones; Shane Giraldo; Allison McGuirk; Mateo Caballero; Allegra R. Gordon (BMC, 2022)
Abstract Background Research shows that transmasculine people experience discrimination based on their gender identity and/or expression (i.e., cissexism) while obtaining health care. However, studies examining the experience of other forms of discrimination in health care settings among diverse subgroups of transmasculine individuals, including those from minoritized racial/ethnic backgrounds, are very limited. Methods Guided by intersectionality, we designed a qualitative research study to explore how transmasculine people of color experience-and resist-multiple, intersecting forms of discrimination in health care settings. Guided by a purposive sampling strategy, we selected 19 transmasculine young adults of color aged 18-25 years to participate in 5 mini-focus groups conducted between February and May 2019 in Boston, MA. Focus group transcripts were analyzed using a template style approach to thematic analysis that involved both deductive and inductive coding using a codebook. Coded text fragments pertaining to participants' experiences of health care discrimination were clustered into themes and sub-themes. Results Transmasculine people of color described experiencing notable challenges accessing physical and mental health care as a result of structural barriers to identifying health care providers with expertise in transgender health, finding providers who share one or more of their social positions and lived experiences, and accessing financial resources to cover high health care costs. Further, participants discussed anticipating and experiencing multiple forms of interpersonal discrimination-both independently and simultaneously-in health care settings, including cissexism, racism, weight-based discrimination, and ableism. Moreover, participants described the negative impact of anticipating and experiencing multiple interpersonal health care discrimination on their health care utilization, quality of care, and mental and physical health. Lastly, participants discussed using various strategies to resist the multiple, intersecting forms of discrimination they encounter in health care settings, including setting boundaries with health care providers, seeking care from competent providers with shared social positions, engaging in self-advocacy, drawing on peer support during health care visits, and obtaining health information through their social networks. Discussion Efforts are needed to address cissexism, racism, weight-based discrimination, ableism, and other intersecting forms of discrimination in clinical encounters, health care institutions and systems, and society in general to advance the health of transmasculine people of color and other multiply marginalized groups.